The Influence of Selfhelp Groups in Enhancing Social Integration and Decision Making among the Widows in Kenya - Birech, Jeniffer Kosgey (Advances in Social Sciences Research Journal, 2018)
The challenges of widowhood continues to be alarming worldwide with the number of widows increasing globally. Widows comprise a significant proportion of 7% to 16% of of all adult women populations. The ratio of widows to that of widowers is as high as 4:1. While the loss of a spouse precipitates disruption of the family, its consequences are not the same for men and women. The widows face social and economic challenges such as loss of income, inheritance of property, participation in social activities and decision making in the family. This paper examines the social challenges with restriction itself to social integration and decision making pointing out the benefits of group participation.The paper is based on the findings of a study carried out among the widows in Kenya.Grounded on social exchange theory by Peter Blau, Social Network theory and the theory of Redefinition of a situation by William Thomas, the study found out that there are more young widows below fourty five years (56%) than older ones. Most (77%) of the widows however belonged and participated in self help groups which had been beneficial, At least 23% did not belong to any group missing out on opportunities. Those in self help groups felt more integrated into the community through participating in projects such as planting trees, attending trainings organized by the groups, visiting one another and selling and buying on behalf of their groups.Their self esteem improved and they could make decisions on behalf of the family. However, it was observed that leadership of the groups is wanting thus needful to equip them with leadership skills. The paper recommends training opportunities by the government, religious organizations and other stakeholders to create awareness on the social integration and encourage all widows to participate.